Pristine and ruthenium-doped TiO2 nanoclusters for nitrogen reduction reaction: Ab initio study of structure and adsorption. (15th February 2023) - Žibert, Taja; Likozar, Blaž; Huš, Matej
Abstract: The Haber-Bosch process has been the workhorse of ammonia synthesis for more than a century, but its environmental cost has instigated the search for greener methods of nitrogen activation. Photocatalysis using doped titanium dioxide (TiO 2 ) stands out as a promising method. In this work, we explore the electronic properties of pristine and Ru-loaded TiO 2 clusters and the activation of nitrogen, hydrogen and ammonia on these clusters. We study the effect of the cluster size and the role of Ru on the electronic properties of the clusters and their activation capabilities. We show that loading with Ru enhanced the nitrogen fixation ability, yet it does not influence the adsorption of hydrogen and ammonia, avoiding catalyst poisoning. Graphical abstract: Highlights: Nitrogen fixation was studied over pristine and Ru-loaded TiO2 nanoclusters. Density functional theory was used to obtain the desired results. Ru doping improves the electronic properties of pristine TiO2 nanoclusters. Ru doping improves the nitrogen fixation ability and activation. The studied clusters are promising candidates for photocatalytic nitrogen fixation.